2019
DOI: 10.1007/s12250-019-00122-3
|View full text |Cite
|
Sign up to set email alerts
|

Viral Regulation of RNA Granules in Infected Cells

Abstract: RNA granules are cytoplasmic, microscopically visible, non-membrane ribo-nucleoprotein structures and are important posttranscriptional regulators in gene expression by controlling RNA translation and stability. TIA/G3BP/PABP-specific stress granules (SG) and GW182/DCP-specific RNA processing bodies (PB) are two major distinguishable RNA granules in somatic cells and contain various ribosomal subunits, translation factors, scaffold proteins, RNA-binding proteins, RNA decay enzymes and helicases to exclude mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 165 publications
(254 reference statements)
2
90
0
2
Order By: Relevance
“…After viral infection, PKR binds to viral double-stranded RNA (dsRNA), which activates the autophosphorylation of the kinase. Activation of PKR phosphorylates eIF2α (15)(16)(17)(18), inhibits the formation of the ternary complex tRNAiMet-GTP-eIF2, and initiates assembly of SGs, thereby preventing cell translation (9,16,17,19). For example, RSV-induced SGs are mediated by PKR-dependent eIF2α phosphorylation (9,20).…”
mentioning
confidence: 99%
“…After viral infection, PKR binds to viral double-stranded RNA (dsRNA), which activates the autophosphorylation of the kinase. Activation of PKR phosphorylates eIF2α (15)(16)(17)(18), inhibits the formation of the ternary complex tRNAiMet-GTP-eIF2, and initiates assembly of SGs, thereby preventing cell translation (9,16,17,19). For example, RSV-induced SGs are mediated by PKR-dependent eIF2α phosphorylation (9,20).…”
mentioning
confidence: 99%
“…This is consistent with previous studies showing that infection with the vaccine strain 17D induces the formation of stress granules in human dendritic cells and hamster kidney cells (53). Thus, formation of stress granules seems to be a general feature of flavivirus infection (35, 36, 54, 55). However, unlike WNV, DENV, ZIKV and the related tick-borne encephalitis virus (35, 36, 38, 5457), YFV does not seem to efficiently antagonize stress granule biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses have adopted several mechanisms to repress the assembly of stress granules and utilize SG protein components for viral polyprotein synthesis instead [74]. For example, herpes simplex virus genome encodes γ 1 34.5 protein that functionally mimics the activity of GADD34 and directs the dephosphorylation of eIF2α [75].…”
Section: Zikv Inhibits Cytoplasmic Stress Granules Formationmentioning
confidence: 99%
“…ZIKV utilized these SG core proteins for viral protein and virion production. Beside regulating eIF2α phosphorylation and hijacking key SG proteins, RNA viruses were reportedly capable of interfering SGs assembly through cleaving and redistributing SGs nucleating factors [74]. It was previously reported that ZIKV NS2B-NS3 protease could cleave host antiviral factors to impair intrinsic host defense; intriguingly, ZIKV did not mediate the cleavage of SG factors even though SGs assembly was affected by ZIKV NS3 and NS2B-NS3 protease [77][78][79][80][81].…”
Section: Zikv Inhibits Cytoplasmic Stress Granules Formationmentioning
confidence: 99%